Pengaruh Kualitas Produk,Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian : : Studi pada Kopi Toko Tua Bandung - Fachruddin Arrazi, Muhammad; Adji, Widwi Handari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
ABSTRACT. This study aims to analyze the relationship between product quality, price, and service quality at Kopi Toko Tua Bandung. Companies in the food and beverage business, particularly those operating in the catering and cafeteria sectors, are often pressed to think of novel and appealing methods to serve their clients. A cafe's ability to entice customers with things like a nice ambiance, unique furnishings, and extras like Instagrammable backgrounds and appealing offers is not to be underestimated. A total of 77 customers of Kopi Toko Tua Bandung participated in questionnaires for this quantitative investigation. The results of the research highlight the significance of product quality, price, and service quality in determining consumers' ultimate purchasing decisions. R-Square for the equation model is 0.843, which indicates it accounts for 84.3% of the variation in customer preferences, and there are no issues with multicollinearity or heteroskedasticity in the data. In conclusion, as competition in the café business heats up, Kopi Toko Tua Bandung must focus on product quality, affordable pricing, and service quality to attract and retain consumers. This study's findings might be useful to cafe operators in responding to shifting tastes and remaining competitive. Keywords: Product Quality, Price, Service Quality, Purchase Decision